Functional, organoleptic assessment and nutritional composition of akara produced from cowpea (Vigna unguiculata)–fonio millet (Digitaria exilis) flour blends - Okorie Emeka Kennedy; Filli Kaleb Bulus; Fatima Jiddum Abdulahi (International Journal of Agricultural Research, Innovation and Technology, 2026)
This study investigated the effect of supplementing cowpea flour with fonio millet flour on the functional, organoleptic, and nutritional properties of akara. Flour blends were analyzed for their pasting and functional properties, while the proximate composition, mineral content, and sensory qualities of the resulting akara were also evaluated. Pure cowpea flour (100%) served as the control and was substituted with fonio millet at varying ratios (5%, 10%, 15%, 20%, 50%, 85%, and 100%). Pasting characteristics such as peak viscosity, trough viscosity, breakdown, final viscosity, setback, peak time, and pasting temperature ranged from 181–1314 RVU, 161–1253 RVU, 8–20 RVU, 292–2905 RVU, 107–1652 RVU, 4.4–6.9 min, and 83.1–87.3°C, respectively. Functional properties, including bulk density, swelling capacity, foam stability, foam capacity, oil and water absorption capacities, and least gelation capacity, showed variation across blends. Substitution with fonio millet increased protein, fat, fiber, and mineral content, while moisture and ash contents remained relatively stable. Sensory analysis revealed high acceptability for akara, particularly from the 90:10 cowpea to fonio millet blend. The findings demonstrate the potential for producing nutritionally enhanced akara using cowpea-fonio blends, thereby promoting local crop utilization and dietary diversity. Int. J. Agril. Res. Innov. Tech. 15(2): 19-24, Dec 2025